2011
DOI: 10.2106/jbjs.j.00634
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Nonoperative Treatment of Craniovertebral Junction Tuberculosis: A Review of Twenty-six Cases

Abstract: Therapeutic Level IV. See Instructions to Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…On one side there are a lot of case descriptions and several case series with more or less cases, all of them with some recommendations regarding classification [19], the establishment of diagnosis and the value of biopsy [13,16,[18][19][20][21]; furthermore, their recommendations are also related to treatment modalities [15,16] and to indications for treatment. Since craniocervical junction tuberculosis carries the risk of secondary instability and severe neuraxis compression [5], sometimes in the sense of severe bulbo-medullary complications [2] with painful torticollis, dysphagia and tetraparesis, early diagnosis is of utmost importance. In rare cases of patients with neurological deficit due to craniocervical junction tuberculosis, a hemiplegia or a monoplegia may occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one side there are a lot of case descriptions and several case series with more or less cases, all of them with some recommendations regarding classification [19], the establishment of diagnosis and the value of biopsy [13,16,[18][19][20][21]; furthermore, their recommendations are also related to treatment modalities [15,16] and to indications for treatment. Since craniocervical junction tuberculosis carries the risk of secondary instability and severe neuraxis compression [5], sometimes in the sense of severe bulbo-medullary complications [2] with painful torticollis, dysphagia and tetraparesis, early diagnosis is of utmost importance. In rare cases of patients with neurological deficit due to craniocervical junction tuberculosis, a hemiplegia or a monoplegia may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Some people recommend conservative treatment only [1,2,5,11,22], others recommend surgery in all patients [3,6,8,23]. Some have shifted their management protocols from surgical to conservative and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…13 In cranio-vertebral junction tuberculosis, despite extensive erosion of the clivus, C1 and C2, and spinal cord compression, the patients can effectively be managed with antituberculosis therapy alone. 9,16 We could deduce that significant cord compression and spinal extension of abscess were significantly associated with outcome in cervical spine tuberculosis. These observations indicated that extensive tuberculous involvement of the spinal cord was responsible for the poor outcome.…”
Section: Discussionmentioning
confidence: 93%
“…8 Even in patients with cranio-vertebral junction tuberculosis, antituberculosis therapy is the mainstay of treatment along with neck stabilization regardless of the extent of bony destruction. 9 If atlantoaxial instability is present, surgery may be contemplated. [10][11][12] Regarding cervical spinal tuberculosis only limited data, either in the form of isolated cases or small case series, are available.…”
Section: Introductionmentioning
confidence: 99%
“…It is known for its ability to present in various forms and guises at different sites [5]. Pyomyositis is the term used to describe a bacterial infection of skeletal muscle with formation of an abscess.…”
Section: Discussion and Treatmentmentioning
confidence: 99%